The Descriptive Analysis of the New Norms of Holistic Consumer Apprentice Program Evaluation - Khairunesa ISA; Sarala Thulasi PALPANADAN; Nurliyana MD ROSNI (Communications of International Proceedings, 2022)
The Covid-19 pandemic and Revolution Industry 4.0 have dramatically contributed to the transformation of the purchasing landscape from conventional to online activities. This may have negative impacts such as an increase of online scammer and fraud. Indirectly it shows that the empowerment level of Malaysian consumerism is at low level especially when some of the consumers are not aware of the consumer’s right and any redress action.  Therefore, The New Norms of Holistic Consumer Apprentice, which was an advocacy program, was organized as an effort to empower the Malaysian consumers. The main objective of the program was to empower the Malaysian consumer. Other objectives were to share and distribute the knowledge and awareness to consumers regarding consumer rights, to share financial literacy, to have the ability to make decision to buy and redress. At the end of the program, an evaluation form was distributed to the participants to ensure the effectiveness of the program and the attainability of the program goals.
Keywords: consumer rights; Malaysian consumers; New Norms of Holistic Consumer Apprentice Program; redress